Gamma interferon and interleukin-10 gene expression in innately susceptible and resistant mice during the early phase of Salmonella typhimurium infection. - Pie, S (1996)
Previous studies have shown that gamma interferon (IFN-gamma) plays a major role in natural resistance to Salmonella typhimurium during the early phase of infection. To assess whether the level of natural resistance in mice is related to the level of IFN-gamma gene expression, we compared IFN-gamma mRNA levels by means of reverse transcriptase-PCR in the spleens of genetically susceptible Itys (C57BL/6 and BALB/c) and resistant Ityr (CBA and DBA/2) mice during the first 5 days of infection. The mRNA expression of interleukin-10 (IL-10), a cytokine which antagonizes IFN-gamma effects, was also investigated. Mice were infected with 10(3) CFU of the virulent strain S. typhimurium C5, a dose which is lethal within a week for susceptible mice only. IFN-gamma mRNA increased to similar levels in both susceptible and resistant mice, suggesting that susceptibility to S. typhimurium infection is not related to defective IFN-gamma gene expression. In contrast, IL-10 mRNA reached much higher levels in susceptible than in resistant mice. Similar results were found in Ity congenic mice, confirming a link between the presence of the Itys allele and a high level of IL-10 gene expression during infection. High levels of IL-10 mRNA in susceptible mice correlated with high IL-10 serum levels (on day 5), whereas IL-10 was not detectable in the sera of resistant mice. However, administration of neutralizing anti-IL-10 monoclonal antibodies did not modify the course of infection. To evaluate the influence of bacterial multiplication on IL-10 mRNA expression, susceptible mice were infected with an attenuated strain of S. typhimurium. This strain induced a low level of IL-10 mRNA expression. When susceptible mice were immunized with an attenuated strain and challenged with the virulent strain, they inhibited the growth of the challenge bacteria and exhibited a low level of IL-10 mRNA. In contrast, when resistant mice were infected with a high (lethal) dose of the virulent strain, they exhibited a high level of IL-10 mRNA. Taken together, these results indicate that the level of IL-10 gene expression correlates with the level of bacterial multiplication in the organs and that the high level of IL-10 mRNA in Itys mice is a consequence rather than the cause of their susceptibility to S. typhimurium infection.